Hamburguesa de pescado enriquecida con EPA y DHA microencapsulado con bajo nivel de sodio - Iman Torres, Alexander Javier (2023)
The increase in non-communicable diseases worldwide requires the food industry to seek strategies that guarantee people's food safety, such as improving the nutritional profiles of new products, replacing saturated fats with polyunsaturated fats, and Sodium reduction from other sales would improve the nutritional profile of any processed product. The present study formulated three hamburger proposals based on hydrobiological species paco (Piaractus brachypomus), boquichico (Prochilodus nigricans), and burjuqui (Chaetobranchus flavescens), partially substituting pork fat with microencapsulated fish oil by complex coacervation, and reducing the sodium level Porcine fat substitution was made in a proportion of 15%. The produced hamburgers were characterized by physicochemical, microbiological, sensory and lipid oxidative stability (TBARS) analyses. Results of 65.36% humidity, 17.77% protein, 17.60% lipid and 150.33mg calcium were obtained. For the fatty acid profile, values of 0.29g of DHA were shown for boquichico hamburger (T2), 0.24g paco hamburger (T1), and 0.20g bujurqui hamburger (T3); for EPA the results obtained were 0.36g (T2), 0.21g (T3), and 0.17g (T1); the statistical analysis shows that there are significant differences between T2, with T1, and T3 (p <0.05). The average acceptance for each hamburger was paco 5.66, boquichico 5.65 and bujurqui 5.64, indicating that the acceptability was above the intermediate value of the scale. The fish burgers have DHA+EPA in values of paco 410mg/100g, boquichico 625mg/100g and bujurqui 410mg/100g, considering them as a food source of omega 3, likewise the burgers are well accepted by direct consumers.